2009
DOI: 10.1002/14651858.cd001402.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for cystic fibrosis

Abstract: al. Early diagnosis of cystic fibrosis through neonatal screening prevents severe malnutrition and improves long-term growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 45 publications
1
48
0
Order By: Relevance
“…Carrier frequency for individuals of Northern European ancestry is around 1 in 25-30 (Williamson 1993). CF affects respiratory, gastrointestinal/digestive, reproductive as well as other systems and, although there is yet no cure, a range of treatments, especially those aimed at reducing the malnutrition (Southern et al 2009), have resulted in increased life expectancies (Dodge et al 2007;O'Sullivan and Freedman 2009). Identification of the CFTR gene associated with CF in 1989 Rommens et al 1989;Riordan et al 1989) led to the introduction of newborn screening in a number of countries.…”
Section: Carrier Screening For Cystic Fibrosismentioning
confidence: 99%
“…Carrier frequency for individuals of Northern European ancestry is around 1 in 25-30 (Williamson 1993). CF affects respiratory, gastrointestinal/digestive, reproductive as well as other systems and, although there is yet no cure, a range of treatments, especially those aimed at reducing the malnutrition (Southern et al 2009), have resulted in increased life expectancies (Dodge et al 2007;O'Sullivan and Freedman 2009). Identification of the CFTR gene associated with CF in 1989 Rommens et al 1989;Riordan et al 1989) led to the introduction of newborn screening in a number of countries.…”
Section: Carrier Screening For Cystic Fibrosismentioning
confidence: 99%
“…Evidence suggests that there is an appreciation of the centrality of communication in ensuring that benefits from NBSPs are realised and the probability of potential harms is reduced. 42,63,[142][143][144][145][146][147][148][149] Specifically, there is a recognised need to inform parents prior to screening, 34,44,52 preferably antenatally. 34,72 Without effective communication the validity of consent is questioned, as, although parents consent to screening, many are not aware that screening has occurred 28,[31][32][33] or have limited knowledge about it.…”
Section: Introductionmentioning
confidence: 99%
“…Newborn screening for cystic fibrosis (NBS) is, despite some evidence of its benefits, (25,26) still controversial (27). Anxiety linked to inconclusive or false-positive test results, risk of premature bacterial colonization, due to earlier exposure to the medical environment, and the hazards of carrier detection in a multiethnic society, are a matter of debate (28).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety linked to inconclusive or false-positive test results, risk of premature bacterial colonization, due to earlier exposure to the medical environment, and the hazards of carrier detection in a multiethnic society, are a matter of debate (28). The actual benefits of NBS appear less clear-cut than for other types of neonatal screening programs (26,28). The Wisconsin randomized clinical trial showed nutritional benefits, but no long-term effects on pulmonary prognosis (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation